2022
DOI: 10.6004/jnccn.2022.0047
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines® Insights: Ovarian Cancer, Version 3.2022

Abstract: Epithelial ovarian cancer is the leading cause of death from gynecologic cancer in the United States, with less than half of patients living >5 years following diagnosis. The NCCN Guidelines for Ovarian Cancer provide recommendations for the diagnosis, evaluation, treatment, and follow-up for patients with ovarian, fallopian tube, and primary peritoneal cancers. These NCCN Guidelines Insights summarize the panel discussion behind recent important updates to the guidelines, including revised guidance on alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
129
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(130 citation statements)
references
References 42 publications
1
129
0
Order By: Relevance
“…For direct application to cancer cells on the peritoneum, IP infusion using anticancer drugs with lower absorption and systemic toxicity, such as paclitaxel and docetaxel, has been studied in various cancers. It is considered effective and safe in treating peritoneal cancer dissemination from ovarian cancer [ 441 442 443 444 445 446 447 ].…”
Section: Treatment For Far Advanced Gastric Cancermentioning
confidence: 99%
“…For direct application to cancer cells on the peritoneum, IP infusion using anticancer drugs with lower absorption and systemic toxicity, such as paclitaxel and docetaxel, has been studied in various cancers. It is considered effective and safe in treating peritoneal cancer dissemination from ovarian cancer [ 441 442 443 444 445 446 447 ].…”
Section: Treatment For Far Advanced Gastric Cancermentioning
confidence: 99%
“…Any time a pelvic ultrasound detects an adnexal lesion, Armstrong et al (6) determining whether the lesion is benign or precancerous is important for guiding subsequent care, which may involve referral to a gynecologic oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…The LION study suggested that lymphadenectomy did not result in longer PFS or OS in patients with advanced ovarian cancer when there were no clinically suspicious abnormal lymph nodes. According to LION, systemic lymphadenectomy does not provide a survival bene t for patients with advanced ovarian cancer whose lymph nodes are visual normal, but increases the risks and complications of surgery; Systematic lymphadenectomy should not be routinely performed in these patients and international guidelines have been rewritten as a result (20).…”
Section: Discussionmentioning
confidence: 99%